The Tapetal Major Facilitator NPF2.8 Is Required for Accumulation of Flavonol Glycosides on the Pollen Surface in Arabidopsis thaliana. Issue 5 (10th March 2020) - Grunewald, Stephan; Marillonnet, Sylvestre; Hause, Gerd; Haferkamp, Ilka; Neuhaus, H. Ekkehard; Veß, Astrid; Hollemann, Thomas; Vogt, Thomas
Abstract : The tapetal major facilitator NPF2.8 is required for accumulation of flavonol glycosides on the pollen surface of Arabidopsis ( Arabidopsis thaliana ). Abstract: The exine of angiosperm pollen grains is usually covered by a complex mix of metabolites including pollen-specific hydroxycinnamic acid amides (HCAAs) and flavonoid glycosides. Although the biosynthetic pathways resulting in the formation of HCAAs and flavonol glycosides have been characterized, it is unclear how these compounds are transported to the pollen surface. In this report we provide several lines of evidence that a member of the nitrate/peptide transporter family is required for the accumulation and transport of pollen-specific flavonol 3-o -sophorosides, characterized by a glycosidic β - 1, 2 -linkage, to the pollen surface of Arabidopsis ( Arabidopsis thaliana ). Ectopic, transient expression in Nicotiana benthamiana epidermal leaf cells demonstrated localization of this flavonol sophoroside transporter (FST1) at the plasmalemma when fused to green fluorescent protein (GFP). We also confirmed the tapetum-specific expression of FST1 by GFP reporter lines driven by the FST1 promoter. In vitro characterization of FST1 activity was achieved by microbial uptake assays based on 14 C-labeled flavonol glycosides. Finally, rescue of an fst1 insertion mutant by complementation with an FST1 genomic fragment restored the accumulation of flavonol glycosides in pollen grains to wild-type levels, corroborating the requirement of FST1 for transport of flavonol-3-o -sophorosides from the tapetum to the pollen surface.